CSIG-02. VAL-083 INHIBITS PROLIFERATION OF A PANEL OF EIGHT GLIOBLASTOMA STEM CELL LINES: DOWNREGULATION OF BDR4 AS A NOVEL ANTI-NEOPLASTIC MECHANISM. (5th November 2018) - Fernandez, Elise; Steino, Anne; Lesser, Glenn; Bacha, Jeffrey; Brown, Dennis; Kwatra, Madan
Abstract: VAL-083 (Dianhydrogalactitol) is a bi-functional DNA targeting agent that is currently being evaluated in a phase II trial in recurrent glioblastoma (GBM) patients. The goal of the present study was to further elucidate the anti-neoplastic effects and signaling pathways through which VAL-083 functions. We examined the efficacy of VAL-083 against a panel of eight GBM stem cells (GSCs) isolated from newly diagnosed GBM patients. The panel of GSCs were molecularly phenotyped based on the expression of several proteins including EGFR, EGFRvIII, and MGMT as well as several stem cell markers including SOX2, NESTIN, MST1, CD133, TFRC, and OLIG2. The effect of VAL-083 on GSC growth was measured using WST-1 reagent and the effect on GSC's ability to form neurospheres was assessed by microscopy. Our results show that VAL-083 inhibits neurosphere formation in all eight GSCs. Further, VAL-083 inhibits the growth of GSCs with an IC50 of 200–2000 nM. To identify the molecular pathways affected by VAL-083, control and VAL-083-treated GSCs were subjected to proteomic analysis using reverse phase protein array (RPPA) technology. The RPPA examined the expression of a total of 297 proteins and phosphoproteins. It was found that VAL-083 affects the expression of several proteins and phosphoproteins central to GBM growth. A key protein significantly downregulated by VAL-083 was bromodomain protein 4 (BRD4). This is a salient important finding because BRD4 has been implicated in several cancers including GBM, and agents that target BRD4 are undergoing development as anti-neoplastic agents. In summary, we report that VAL-083 is effective in halting the growth of a panel of GSC isolated from newly diagnosed GBM patients and the underlying mechanism involves downregulation of BRD4.